2006
DOI: 10.1007/s00259-006-0127-1
|View full text |Cite
|
Sign up to set email alerts
|

The value of FDG-PET in patients with painful total knee arthroplasty

Abstract: Diffuse synovial and focal extrasynovial FDG-PET uptake is commonly found in patients with malrotation of the femoral component and is not related to pain location. The information provided by FDG-PET does not contribute to the diagnosis and management of individual patients with persistent pain after total knee replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 34 publications
(49 reference statements)
1
14
0
1
Order By: Relevance
“…Thus, 20 studies remained for possible inclusion and were retrieved in full-text version. After reviewing the full article, five articles [18,21,22,25,26] were excluded because the same data were used in another article comprising a larger number of patients, one article was excluded because it did not investigate the diagnostic performance of FDG-PET in detecting prosthetic hip or knee joint infection [14], one article [16] was excluded because the same data were used in another article providing more study details, one article [29] was excluded because less than 15 patients with hip and/or knee prosthesis were investigated, and one article [31] was excluded because it appeared to be an abstract only. Screening references of the remaining articles resulted in one other potentially relevant article [32].…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 20 studies remained for possible inclusion and were retrieved in full-text version. After reviewing the full article, five articles [18,21,22,25,26] were excluded because the same data were used in another article comprising a larger number of patients, one article was excluded because it did not investigate the diagnostic performance of FDG-PET in detecting prosthetic hip or knee joint infection [14], one article [16] was excluded because the same data were used in another article providing more study details, one article [29] was excluded because less than 15 patients with hip and/or knee prosthesis were investigated, and one article [31] was excluded because it appeared to be an abstract only. Screening references of the remaining articles resulted in one other potentially relevant article [32].…”
Section: Literature Searchmentioning
confidence: 99%
“…Reviewing titles and abstracts from PubMed/MEDLINE revealed 20 articles potentially eligible for inclusion [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Reviewing titles and abstracts from Embase revealed 17 articles potentially eligible for inclusion, which were all already identified by the PubMed/MEDLINE search.…”
Section: Literature Searchmentioning
confidence: 99%
“…In another study performed by our group, FDG uptake was examined in 28 patients with painful total knee arthroplasty, with uptake found to be related to the location of soft-tissue pain [39]. Increased FDG uptake was found in the synovial membrane in all patients except one patient independent of the clinical diagnosis (Fig.…”
Section: Prosthetic-joint Infectionmentioning
confidence: 98%
“…The results of other investigations have been less satisfactory (71)(72)(73)(74)(75)(76)(77) (73) and that periprosthetic 18 F-FDG accumulation around a knee arthroplasty was not specific for infection (74). Delank et al (75) concluded that 18 F-FDG PET was not specific for lower-extremity joint arthroplasty infection.…”
Section: Prosthetic Joint Infectionmentioning
confidence: 99%